Situation report on Nepal’s agrifood systems: March 2024 - Palikhe, A.; Gupta, S.; Maharjan, N.K.; Adhikari, M.; Kumar, A.; Minot, Nicholas; Koirala, Pankaj; Krupnik, Timothy J. (CSISA, 2024)
In February 2024, Nepal saw moderate inflation with year-on-year figures for overall consumer inflation at 5.0 percent and food and beverage inflation at 6.5 percent. Prices for cereals, pulses, and legumes rose, with spices surging by 32.1 percent. Staple food prices such as rice, wheat flour, lentils, and black beans stayed stable in January 2024. Seasonal price trend analysis from 2002 to 2023 showed that national coarse rice prices in Nepal and its Western provinces were below yearly averages in the first half. However, medium grain rice prices in Western provinces exceeded the yearly average in the first quarter, contrary to typical trends. Labor migration declined by 21.5 percent from July to February, signaling a reduction in out-migration from Nepal. 11.8 percent of this drop occurred in February 2024 compared to the previous month.